Freudig in die Schlacht - Emotionen als Codes für die recta intentio im gerechten Krieg (8.- 10. Jahrhundert) - Foerster, Anne (Emotionen im Krieg - Krieg der Emotionen)

The Swineherd’s Wife who Scolded the King - Foerster, Anne (Women in Early Medieval England)

Eadburh of Wessex - Foerster, Anne (Women in Early Medieval England)

Seaxburh - Foerster, Anne (Women in Early Medieval England)

Struktur und Sonderbauten der Silberbergbaustädte des 16. Jahrhunderts. Zur Korrelation von Städtebau und Montanwesen (Potosí und das Erzgebirge) - Silvestri, Marco (Bergbau und Hausbau)

Quantum 2-SAT on low dimensional systems is $\mathsf{QMA}_1$-complete: Direct embeddings and black-box simulation - Rudolph, Dorian; Gharibian, Sevag; Nagaj, Daniel (arXiv:2401.02368)
Despite the fundamental role the Quantum Satisfiability (QSAT) problem has played in quantum complexity theory, a central question remains open: At which local dimension does the complexity of QSAT transition from "easy" to "hard"? Here, we study QSAT with each constraint acting on a $k$-dimensional and $l$-dimensional qudit pair, denoted $(k,l)$-QSAT. Our first main result shows that, surprisingly, QSAT on qubits can remain $\mathsf{QMA}_1$-hard, in that $(2,5)$-QSAT is $\mathsf{QMA}_1$-complete. In contrast, $2$-SAT on qubits is well-known to be poly-time solvable [Bravyi, 2006]. Our second main result proves that $(3,d)$-QSAT on the 1D line with $d\in O(1)$ is also $\mathsf{QMA}_1$-hard. Finally, we initiate the study of 1D $(2,d)$-QSAT by giving a frustration-free 1D Hamiltonian with a unique, entangled ground state. Our first result uses a direct embedding, combining a novel clock construction with the 2D circuit-to-Hamiltonian construction of [Gosset, Nagaj, 2013]. Of note is a new simplified and analytic proof for the latter (as opposed to a partially numeric proof in [GN13]). This exploits Unitary Labelled Graphs [Bausch, Cubitt, Ozols, 2017] together with a new "Nullspace Connection Lemma", allowing us to break low energy analyses into small patches of projectors, and to improve the soundness analysis of [GN13] from $Ω(1/T^6)$ to $Ω(1/T^2)$, for $T$ the number of gates. Our second result goes via black-box reduction: Given an arbitrary 1D Hamiltonian $H$ on $d'$-dimensional qudits, we show how to embed it into an effective null-space of a 1D $(3,d)$-QSAT instance, for $d\in O(1)$. Our approach may be viewed as a weaker notion of "simulation" (à la [Bravyi, Hastings 2017], [Cubitt, Montanaro, Piddock 2018]). As far as we are aware, this gives the first "black-box simulation"-based $\mathsf{QMA}_1$-hardness result, i.e. for frustration-free Hamiltonians.

Hilfst du mir, so hilfst du dir. Diplomatische Überzeugungsstrategien der Regentin Christine Charlotte von Ostfriesland gegenüber Kaiser Leopold I. im 17. Jahrhundert (erscheint 2024) - Becker, Rieke (Österreichische Zeitschrift für Geschichtswissenschaften. Themenband „New Diplomatic History“)
Keywords: New Diplomatic History; Neue Diplomatiegeschichte

Materialschonende Verarbeitung von Thermoplasten auf Wave-Schnecken - Schall, Christoph Wilhelm Theodor
Die Extrusion stellt das mengenmäßig dominante Verarbeitungsverfahren für thermoplastische Kunststoffe dar. Daher gibt es starke Bestrebungen in diesem Bereich hin zu einer höheren Wirtschaftlichkeit, welche beispielsweise durch höheren Massedurchsatz bei gleichbleibender Maschinengröße erreicht werden kann, oder aber auch im Hinblick auf eine Kreislaufwirtschaft die Bestrebung hin zu einer materialschonenden Verarbeitung. Beide Bestrebungen erfordern spezielle Schneckenkonzepte. Hierunter fallenWave- Schnecken, welche in beiden Bereichen ein vorteilhaftes Prozessverhalten aufzeigen sollen. Die Auslegung von Wave-Schnecken erfordert jedoch ein stärkeres Verständnis über das geometrieabhängige Prozessverhalten in der Extrusion. Im Rahmen der Dissertation werden zwei Themengebiete angegangen. Das erste Thema ist die Herleitung einer Methode zur Charakterisierung des Abbauverhaltens von Thermoplasten sowie die Nutzung der Charakterisierung als Vorhersagemodell. Das zweite Thema behandelt die Auslegung von Wave-Schnecken basierend auf numerischen Simulationen samt Validierung anhand von sieben Energy-Transfer-Schnecken im Vergleich zu drei konventionellen Schnecken. Hierbei werden unter anderem der Materialabbau, die thermische und die stoffliche Homogenität betrachtet, um ein umfassendes Bild über das Prozessverhalten der Schnecken zu schaffen. Die vorgestellten Untersuchungen dienen schlussendlich zu einer Bestätigung des vorteilhaften Prozessverhaltens von Wave-Schnecken.

COVID-19 in Female and Male Athletes: Symptoms, Clinical Findings, Outcome, and Prolonged Exercise Intolerance—A Prospective, Observational, Multicenter Cohort Study (CoSmo-S) - Widmann, Manuel; Gaidai, Roman; Schubert, Isabel; Grummt, Maximilian; Bensen, Lieselotte; Kerling, Arno; Quermann, Anne; Zacher, Jonas; Vollrath, Shirin; Bizjak, Daniel Alexander; Beckendorf, Claudia; Egger, Florian; et al. (Sports Medicine)
Abstract Background An infection with SARS-CoV-2 can lead to a variety of symptoms and complications, which can impair athletic activity. Objective We aimed to assess the clinical symptom patterns, diagnostic findings, and the extent of impairment in sport practice in a large cohort of athletes infected with SARS-CoV-2, both initially after infection and at follow-up. Additionally, we investigated whether baseline factors that may contribute to reduced exercise tolerance at follow-up can be identified. Methods In this prospective, observational, multicenter study, we recruited German COVID elite-athletes (cEAs, n = 444) and COVID non-elite athletes (cNEAs, n = 481) who tested positive for SARS-CoV-2 by PCR (polymerase chain reaction test). Athletes from the federal squad with no evidence of SARS-CoV-2 infection served as healthy controls (EAcon, n = 501). Questionnaires were used to assess load and duration of infectious symptoms, other complaints, exercise tolerance, and duration of training interruption at baseline and at follow-up 6 months after baseline. Diagnostic tests conducted at baseline included resting and exercise electrocardiogram (ECG), echocardiography, spirometry, and blood analyses. Results Most acute and infection-related symptoms and other complaints were more prevalent in cNEA than in cEAs. Compared to cEAs, EAcon had a low symptom load. In cNEAs, female athletes had a higher prevalence of complaints such as palpitations, dizziness, chest pain, myalgia, sleeping disturbances, mood swings, and concentration problems compared to male athletes ( p < 0.05). Until follow-up, leading symptoms were drop in performance, concentration problems, and dyspnea on exertion. Female athletes had significantly higher prevalence for symptoms until follow-up compared to male. Pathological findings in ECG, echocardiography, and spirometry, attributed to SARS-CoV-2 infection, were rare in infected athletes. Most athletes reported a training interruption between 2 and 4 weeks (cNEAs: 52.9%, cEAs: 52.4%), while more cNEAs (27.1%) compared to cEAs (5.1%) had a training interruption lasting more than 4 weeks ( p < 0.001). At follow-up, 13.8% of cNEAs and 9.9% of cEAs ( p = 0.24) reported their current exercise tolerance to be under 70% compared to pre-infection state. A persistent loss of exercise tolerance at follow-up was associated with persistent complaints at baseline, female sex, a longer break in training, and age > 38 years. Periodical dichotomization of the data set showed a higher prevalence of infectious symptoms such as cough, sore throat, and coryza in the second phase of the pandemic, while a number of neuropsychiatric symptoms as well as dyspnea on exertion were less frequent in this period. Conclusions Compared to recreational athletes, elite athletes seem to be at lower risk of being or remaining symptomatic after SARS-CoV-2 infection. It remains to be determined whether persistent complaints after SARS-CoV-2 infection without evidence of accompanying organ damage may have a negative impact on further health and career in athletes. Identifying risk factors for an extended recovery period such as female sex and ongoing neuropsychological symptoms could help to identify athletes, who may require a more cautious approach to rebuilding their training regimen. Trial Registration Number DRKS00023717; 06.15.2021—retrospectively registered.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Swing-up dynamics in quantum emitter cavity systems: Near ideal single photons and entangled photon pairs - Heinisch, Nils; Köcher, Nikolas; Bauch, David; Schumacher, Stefan (Physical Review Research)

BelgienNet – une plateforme pour l’accès aux langues et cultures de la Belgique - Huybrechts, Yves; Karaca, Resul (Synergies Pays germanophones)

Corrosion behaviour of self-piercing riveted joints with uncoated rivets in high nitrogen steel - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson (Production Engineering)

Historisches Lernen in einer ‚(Geschichts-)Kultur der Digitalität‘? - Hartung, Olaf (Geschichtskulturen im digitalen Wandel?)

Geschichtskulturen im digitalen Wandel?

Het verhaal van Vlaanderen. Analyse van het mediaformat en het geschiedverhaal - Huybrechts, Yves; Schmitz, Sabine (bmgn — Low Countries Historical Review)

Die Vorgeschichte der „sozialen Medien“. Über die Träume digitaler Vergemeinschaftung und freier Kommunikation - Schmitt, Martin (Soziale Medien – wie sie wurden, was sie sind)
Sind „soziale Medien“ überhaupt ein Thema für die Geschichtswissenschaft? Ja, denn die längere Geschichte der Digitalisierung, in der die „sozialen Medien“ einzuordnen sind, zählt bereits über 80 Jahre. Konrad Zuse und andere Ingenieure entwickelten seit 1941 die ersten Digitalcomputer, Unternehmer*innen, Wissenschaftler*innen und Staatenlenker*innen setzten diese seit den 1950er Jahren für ihre Zwecke ein, die Zivilgesellschaft adaptierte sie in den darauffolgenden Dekaden – all das prägte die sozio-digitale Landschaft der späteren „sozialen Medien“. Als unmittelbar „nach dem Boom“ etwa um 1970 zahlreiche Industriegesellschaften einen strukturellen Wandel in Wirtschaft, Gesellschaft und Politik durchlebten, war eine Antwort darauf die vermehrte Digitalisierung und Vernetzung. Daraus entwickelte sich die 1990er Jahre als markante Dekade von World Wide Web, Google und Chatdiensten. Die Entwicklung der „sozialen Medien“ ist also unter anderem in eine ökonomische und gesellschaftliche Entwicklung der Aufmerksamkeitsökonomie und in die längeren Veränderungen von Wirtschafts- und Gesellschaftsordnungen der Ausdifferenzierung und partiellen Individualisierung seit den 1960er Jahren einzuordnen. Dadurch lässt sich besser verstehen, welche Prämissen ihnen zugrunde lagen, welche Möglichkeitsräume und Probleme sich daraus ergaben und warum sie die heutige Öffentlichkeit in einer bestimmten Art und Weise dominieren – ohne sie jedoch zu determinieren.
Keywords: Digitalgeschichte; Soziale Medien; Technikgeschichte; World Wide Web; Digitalisierung

Alles geht? Die jüngste Geschichte der „sozialen Medien“. Zwischen Wirtschaft und Gemeinschaft - Schmitt, Martin (Soziale Medien – wie sie wurden, was sie sind)
Twitter ist jetzt X und befindet sich auf dem absteigenden Ast. Auf diesem Ast sitzt Facebook bereits seit längerem. Der Kurzvideodienst Vine, Vorgänger von TikTok, ist Geschichte. Und auch bei Google klingeln die Alarmglocken angesichts der „neuen“ Konkurrenz durch Microsoft und ChatGPT. Umso dringlicher wird also die Historisierung der „sozialen Medien“, das heißt, sie in ihren historischen Kontext einzuordnen und ihren Mythos zu entzaubern. Dabei wartet das Vorhaben mit einer doppelten Herausforderung auf: Erstens, dass es sich bei den Unternehmen der Branche und zweitens auch bei den dort gebildeten Gemeinschaften um recht flüchtige, wandelhaften Gestalten handelt. Scheitern und Wandel ist Teil der „sozialen Medien“ – und sei es nur in der schnellen Abfolge der Moden des „nächsten großen Dings“. Dementsprechend versucht dieser Beitrag mit einem systematischeren Ansatz als dem der gesellschaftlichen Selbstbeschreibung, die Entwicklung des sozio-digitalen Phänomens „soziale Medien“ in dessen Zeitkontext einzuordnen.
Keywords: Digitalgeschichte; Soziale Medien; Technikgeschichte; Wirtschaftsgeschichte; Digitalisierung; Twitter; Facebook; Meta

Edge-Connectivity and Pairwise Disjoint Perfect Matchings in Regular Graphs - Ma, Yulai; Mattiolo, Davide; Steffen, Eckhard; Wolf, Isaak Hieronymus (Combinatorica)
For 0 ≤ t ≤ r let m(t, r) be the maximum number s such that every t-edge-connected r-graph has s pairwise disjoint perfect matchings. There are only a few values of m(t, r) known, for instance m(3, 3) = m(4, r) = 1, and m(t, r) ≤ r − 2 for all t = 5, and m(t, r) ≤ r − 3 if r is even. We prove that m(2l, r) ≤ 3l − 6 for every l ≥ 3 and r ≥ 2l.
Keywords: Computational Mathematics; Discrete Mathematics and Combinatorics

Decomposing large unitaries into multimode devices of arbitrary size - Arends, Christian; Wolf, Lasse Lennart; Meinecke, Jasmin; Barkhofen, Sonja; Weich, Tobias; Bartley, Tim (Physical Review Research)
Keywords: General Physics and Astronomy

Experimentelle und simulative Analyse der Mischwirkung in Einschneckenextrudern - Schadomsky, Michael

Zwischen Beutesuche und politischen Ambitionen. Die Normannen an Rhein und Maas zwischen 880 und 892 - Kamp, Hermann (Zeitschrift des Aachener Geschichtsvereins)

‚Schelmische‘ Post-DDR-Romane: Ingo Schulzes „Peter Holtz“ und Lea Streisands „Hufeland, Ecke Bötzow“ - Elit, Stefan (‚Topographisches‘ Schreiben: Lea Streisand, Paderborn, Wintersemester 2022/2023)

'Topographisches‘ Schreiben: Lea Streisand. Paderborn Wintersemester 2022/23

‚Topographisches‘ Schreiben. Lea Streisand, Paderborn Wintersemester 2022/23: Die 41. Gastdozentur für Schriftstellerinnen und Schriftsteller. Zur Einführung. - Eke, Norbert (‚Topographisches‘ Schreiben: Lea Streisand – Paderborn Wintersemester 2022/23)

Sich selbst erzählen. Lea Streisands autofiktionales Erzählen. - Eke, Norbert (‚Topographisches‘ Schreiben: Lea Streisand – Paderborn Wintersemester 2022/23)

Scalable quantum detector tomography by high-performance computing - Schapeler, Timon; Schade, Robert; Lass, Michael; Plessl, Christian; Bartley, Tim (arXiv:2404.02844)
At large scales, quantum systems may become advantageous over their classical counterparts at performing certain tasks. Developing tools to analyse these systems at the relevant scales, in a manner consistent with quantum mechanics, is therefore critical to benchmarking performance and characterising their operation. While classical computational approaches cannot perform like-for-like computations of quantum systems beyond a certain scale, classical high-performance computing (HPC) may nevertheless be useful for precisely these characterisation and certification tasks. By developing open-source customised algorithms using high-performance computing, we perform quantum tomography on a megascale quantum photonic detector covering a Hilbert space of $10^6$. This requires finding $10^8$ elements of the matrix corresponding to the positive operator valued measure (POVM), the quantum description of the detector, and is achieved in minutes of computation time. Moreover, by exploiting the structure of the problem, we achieve highly efficient parallel scaling, paving the way for quantum objects up to a system size of $10^{12}$ elements to be reconstructed using this method. In general, this shows that a consistent quantum mechanical description of quantum phenomena is applicable at everyday scales. More concretely, this enables the reconstruction of large-scale quantum sources, processes and detectors used in computation and sampling tasks, which may be necessary to prove their nonclassical character or quantum computational advantage.

Asymptotic behavior of solutions to the extension problem for the fractional Laplacian on noncompact symmetric spaces - Papageorgiou, Efthymia (Journal of Evolution Equations)
Abstract This work deals with the extension problem for the fractional Laplacian on Riemannian symmetric spaces G / K of noncompact type and of general rank, which gives rise to a family of convolution operators, including the Poisson operator. More precisely, motivated by Euclidean results for the Poisson semigroup, we study the long-time asymptotic behavior of solutions to the extension problem for $$L^1$$ L 1 initial data. In the case of the Laplace–Beltrami operator, we show that if the initial data are bi- K -invariant, then the solution to the extension problem behaves asymptotically as the mass times the fundamental solution, but this convergence may break down in the non-bi- K -invariant case. In the second part, we investigate the long-time asymptotic behavior of the extension problem associated with the so-called distinguished Laplacian on G / K . In this case, we observe phenomena which are similar to the Euclidean setting for the Poisson semigroup, such as $$L^1$$ L 1 asymptotic convergence without the assumption of bi- K -invariance.
Keywords: Mathematics (miscellaneous)

Virtuelle Ensembles. Große Musik in kleinen Kacheln mit der Acapella-App - Gosmann, Phillip (Musik und Unterricht)

The association between dairy intake in adolescents with inflammation and risk markers of type 2 diabetes during young adulthood – results of the DONALD study - Hohoff, E; Jankovic, N; Perrar, I; Schnermann, ME; Herder, C; Nöthlings, U; Libuda, Lars; Alexy, U (Public Health Nutrition)
ABSTRACT OBJECTIVE: The aim of this analysis was to investigate whether habitual intake of total dairy (TD) or different dairy types (liquid, solid, fermented, not-fermented, low-fat, high-fat, low-sugar and high-sugar dairy) during adolescence is associated with biomarkers of low-grade inflammation as well as risk factors of type 2 diabetes in young adulthood. DESIGN: Multivariable linear regression analyses were used to investigate prospective associations between estimated TD intake as well as intake of different types of dairy and a pro-inflammatory score, based on hsCRP, IL-6, IL-18, leptin and adiponectin, and insulin resistance assessed as HOMA2-IR in an open cohort study. SETTING: Dortmund, Germany PARTICIPANTS: Data from participants (n=375) of the DOrtmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study were included, for whom at least two 3-day weighed dietary records during adolescence (median age: 11 years) and one blood sample in young adulthood (>18 years) were available. RESULTS: There was no statistically significant association between TD intake or intake of any dairy type and the pro-inflammatory score (all p>0.05). TD intake as well as each dairy type intake and insulin resistance also showed no association (all p>0.05). CONCLUSIONS: The habitual intake of dairy or individual types of dairy during adolescence does not seem to have a major impact on low-grade systemic inflammation and insulin resistance in the long term. There was no indication regarding a restriction of dairy intake for healthy children and adolescents in terms of diabetes risk reduction.
Keywords: Public Health; Environmental and Occupational Health; Nutrition and Dietetics; Medicine (miscellaneous)

Modellierungen außerinstitutioneller Aneignungsprozesse digital-materieller Interfaces und (musik-)pädagogische Anschlüsse - Neuhausen, Timo; Ahlers, Michael (Musik – Digitalisierung – Bildung)

Singen auf TikTok und Co. Sind Gesangspraktiken in (post)digitaler Kultur (k)ein Thema für die Musikpädagogik? - Godau, Marc (Stimme, Medien, Umwelt. Kinder- und Jugendstimme)

Liveness-Norm in der Musikpädagogik – warum die Orientierung an Live-Musik kulturelle Vielfalt und Digitalisierung verhindert - Godau, Marc; Gosmann, Phillip (Seminar)

“Der Draht ist gut, hält uns ab vom dummen Leben“. Ironisierung als kommunikativer Versuch des Umgangs mit Entwertungs- und Gewalterfahrungen durch jüdische Textproduzenten im Getto Litzmannstadt - Markewitz, Friedrich (Invective Discourse)
Immediately after the National Socialist seizure of power, a comprehen-sive social, legal and ultimately existential exclusion of Jewish people began. The disturbing perception of the break-up of previous understandings of the world was intensified against the background of the acts of annihilation by the National Socialists. Countering this in a communicative form became an often agonizing challenge for Jewish speakers, but also a necessary need. This paper will focus on a communicative phenomenon that has been little researched in linguistics so far: The use of irony to counter experiences of devaluation and violence. By eval-uating ironic utterances in textual communications of the Litzmannstadt ghetto, the criticism of elements of National Socialist ideology will be tentatively made understandable, as well as the experiences of violence within the ghetto.

Haus oder Schule? oder Haus und Schule? Zur kulturell-gesellschaftlichen Bedeutung der historischen Textsorte 'Schulprogramm' hinsichtlich der Konstitution, Festigung wie Abgrenzung des Erziehungssystems im 19. Jahrhundert - Markewitz, Friedrich (Textsorten in Sprach-, Kultur- und Sozialgeschichte)

Ironie - Markewitz, Friedrich
Ironie lässt sich als uneigentliches Kommunikationsmittel beschreiben, mit dem etwas anderes zum Ausdruck gebracht wird, als Sprecher*innen oder Schreiber*innen eigentlich meinen. Dies erfordert eine Differenzierung in Gesagtes und Gemeintes. Doch diese Differenzierung ist längst nicht immer eindeutig und so lebt Ironie von einer interpretatorischen Ambivalenz, ob eine Äußerung wörtlich oder ironisch zu verstehen ist. Aufgrund dieser Ambivalenz und ihrer kulturgeschichtlichen Entwicklung erscheint Ironie als ebenso faszinierendes wie komplexes Sprach-Phänomen. Die vorliegende Einführung gibt aus kulturlinguistischer Perspektive Einblicke in die verschiedenen Möglichkeiten der theoretischen Beschreibung, methodischen Erfassung sowie empirischen Analyse von Ironie. Dabei werden einerseits alltagssprachliche Formen ironischen Kommunizierens in den Blick genommen, andererseits Möglichkeiten des interdisziplinären Anschlusses, um Ironie als linguistisches sowie als kulturgeschichtliches Phänomen zugänglich zu machen.

§ 6 (Kartellrechtliche Grenzen der Kommanditgesellschaft) - Bartlitz, David (Münchener Handbuch des Gesellschaftsrechts)

Further information about neural valence-dependent processing of augmented feedback in extensive motor practice: An analysis of frontal theta-band activity - Margraf, Linda; Krause, Daniel; Weigelt, Matthias

Religion und Freiheit - Süßmann, Johannes

Realization of high-fidelity unitary operations on up to 64 frequency bins - De, Syamsundar; Ansari, Vahid; Sperling, Jan; Barkhofen, Sonja; Brecht, Benjamin; Silberhorn, Christine (Physical Review Research)
The ability to apply user-chosen large-scale unitary operations with high fidelity to a quantum state is key to realizing future photonic quantum technologies. Here, we realize the implementation of programmable unitary operations on up to 64 frequency-bin modes. To benchmark the performance of our system, we probe different quantum walk unitary operations, in particular, Grover walks on four-dimensional hypercubes with similarities exceeding 95% and quantum walks with 400 steps on circles and finite lines with similarities of 98%. Our results open a path toward implementing high-quality unitary operations, which can form the basis for applications in complex tasks, such as Gaussian boson sampling. Published by the American Physical Society 2024

Inklusion verstehen - Szenen aus dem Unterricht in interdisziplinärer Reflexion
Die Verankerung von Inklusion als Querschnittsthema lehramtsbezogener Studiengänge fordert zu einer interdisziplinären Verständigung über die Vorstellung inklusiver Unterrichtsgestaltung heraus. Die ForscherInnengruppe der Universität Paderborn wählt hierfür als methodischen Ausgangspunkt Vignetten als verdichtete Fallbeispiele aus der Unterrichtspraxis, die aus verschiedenen fachübergreifenden praxistheoretischen Perspektiven gelesen und so gemeinsam diskutiert werden. In der Linie praxistheoretischer Arbeiten reflektiert das Buch Praktiken im inklusiven Fachunterricht in der Spannung zu den normativen (sonder-)pädagogischen bzw. (fach-)didaktischen Vorannahmen, um aus dieser Reflexion eigenes verantwortetes Handeln zu entwickeln. Die Vignettenbündel laden so zum diskursiven Austausch, zur Kontrastierung oder zum "Einfangen" selbst erlebter Unterrichtspraxen auf dem Weg des Verstehens von Inklusion in Theorie und Praxis ein.

Glycemic response to meals with a high glycemic index differs between morning and evening: a randomized cross-over controlled trial among students with early or late chronotype - Stutz, Bianca; Krueger, Bettina; Goletzke, Janina; Jankovic, Nicole; Alexy, Ute; Herder, Christian; Dierkes, Jutta; Berg-Beckhoff, Gabriele; Jakobsmeyer, Rasmus; Reinsberger, Claus; Buyken, Anette (European Journal of Nutrition)
Abstract Purpose Glycemic response to the same meal depends on daytime and alignment of consumption with the inner clock, which has not been examined by individual chronotype yet. This study examined whether the 2-h postprandial and 24-h glycemic response to a meal with high glycemic index (GI) differ when consumed early or late in the day among students with early or late chronotype. Methods From a screening of 327 students aged 18–25 years, those with early (n = 22) or late (n = 23) chronotype participated in a 7-day randomized controlled cross-over intervention study. After a 3-day observational phase, standardized meals were provided on run-in/washout (days 4 and 6) and intervention (days 5 and 7), on which participants received a high GI meal (GI = 72) in the morning (7 a.m.) or in the evening (8 p.m.). All other meals had a medium GI. Continuous glucose monitoring was used to measure 2-h postprandial and 24-h glycemic responses and their variability. Results Among students with early chronotype 2-h postprandial glucose responses to the high GI meal were higher in the evening than in the morning (iAUC: 234 (± 92) vs. 195 (± 91) (mmol/L) × min, p = 0.042). Likewise, mean and lowest 2-h postprandial glucose values were higher when the high GI meal was consumed in the evening (p < 0.001; p = 0.017). 24-h glycemic responses were similar irrespective of meal time. Participants with late chronotype consuming a high GI meal in the morning or evening showed similar 2-h postprandial (iAUC: 211 (± 110) vs. 207 (± 95) (mmol/L) × min, p = 0.9) and 24-h glycemic responses at both daytimes. Conclusions Diurnal differences in response to a high GI meal are confined to those young adults with early chronotype, whilst those with a late chronotype seem vulnerable to both very early and late high GI meals. Registered at clinicaltrials.gov (NCT04298645; 22/01/2020).

Wirtschafts- und Finanzpolitik als Schlüsselbereiche europäischer Einigung - Schönhärl, Korinna; Leucht, Brigitte (Europäische Einigung zwischen Anspruch und Wirklichkeit. Eine historische Bestandsaufnahme)
Im Gespräch loten Brigitte Leucht und Korinna Schönhärl aus, welche Rolle wirtschafts- und finanzpolitische Überlegungen und Faktoren für den europäischen Einigungsprozess gespielt haben und immer noch spielen.
Keywords: Wirtschaftsgeschichte; Europäische Geschichte; Europäische Einigung; Staatsverschuldung; Moderne griechische Geschichte

Alexandra Treder (Universität Paderborn) rezensiert: Döll, Marion & Michalak, Magdalena (2023): Deutsch als Zweitsprache und inklusive Bildung. [Deutsch als Zweitsprache – Positionen, Perspektiven, Potenziale, Bd. 3]. Münster: Waxmann, 142 Seiten. ISBN 978-3-8309-4711-0. - Treder, Alexandra (Forschungsportal für Spracherwerb und Migration (daz-portal))

Histories of Tax Evasion, Avoidance and Resistance - Schönhärl, Korinna; Hürlimann, Gisela; Rohde, Dorothea
Tax evasion, tax avoidance and tax resistance are widespread phenomena in political, economic, social and fiscal history from antiquity through medieval, early modern and modern times. Histories of Tax Evasion, Avoidance and Resistance shows how different groups and individuals around the globe have succeeded or failed in not paying their due taxes, whether in kind or in cash, on their properties or on their crops. It analyses how, throughout history, wealthy and poor taxpayers have tried to avoid or reduce their tax burden by negotiating with tax authorities, through practices of legal or illegal tax evasion, by filing lawsuits, seeking armed resistance or by migration, and how state authorities have dealt with such acts of claim making, defiance, open resistance or elusion. It fills an important research gap in tax history, addressing questions of tax morale and fairness, and how social and political inequality was negotiated through taxation. It gives rich insights into the development of citizen-state relationships throughout the course of history. The book comprises case studies from Ancient Athens, Roman Egypt, Medieval Europe, Early Modern Mexico, the Ottoman Empire, Nigeria under British colonial rule, the United Kingdom of the early 20th century, Greece during the Second World War, as well as West Germany, Switzerland, Sweden and the United States in the 20th century, including transnational entanglements in the world of late-modern offshore finance and taxation. The authors are experts in fiscal, economic, financial, legal, social and/or cultural history. The book is intended for students, researchers and scholars of economic and financial history, social and world history and political economy. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Share Alike 4.0 license.
Keywords: Tax History; Financial History

The Ability and Intention of Not Paying Taxes in History. Some Introductory Observations - Schönhärl, Korinna; Hürlimann, Gisela; Rohde, Dorothea (Histories of Tax Evasion, Avoidance and Resistance)
Jean Bodin's list on how the absolutist monarchical state could raise its revenue ranked taxation only in seventh place. From a modern legal perspective, taxes are compulsory transfers of resources that households and enterprises pay to one or several government bodies without receiving an individual, specific benefit in return. Historians have dealt with not paying taxes in various contexts, such as analysing tax resistance and tax resistance movements in history. Tax law is best understood as an outcome of long-term, often conflictual, negotiations and as an expression of specific political mentalities and ideologies. As a consequence, tax law and sometimes even the tax juridical system have a strongly politicised character. Loopholes in tax legislation that enable or facilitate avoidance or evasion can thus be regarded as a result of the interest-driven politics of parliamentary majorities, as the success of concerted lobby pressure.

How to Create a Taxpaying Spirit. A Transnational Examination of an US American and a Western German Tax Education Film in and after World War II - Schönhärl, Korinna (Histories of Tax Evasion, Avoidance and Resistance)
As a case study, this chapter examines two tax education films that were produced 11 years apart in the USA and Western Germany during and after World War II: “The New Spirit” and “Putzke wants to know”. In contrast to America's most popular cartoon character 11 years earlier, Erwin Putzke is in a terrible mood at the beginning of the short film “Putzke wants to know”. The family father and electrician with a workshop of his own is annoyed and upset by the duty of filling in his tax return, grumbling at his wife and daughter and even at their budgie. The film's tax morale message is conveyed to its audience against the backdrop of a sober post-war reality characterised by allied occupation and the Allies' say in West German tax policies during a period of laborious economic build-up after a lost war.

Bibliotheken des Hellwegraums als Orte frühneuzeitlichen Kulturtransfers. Aufriß und Forschungsprogramm - Süßmann, Johannes (Bücher in Westfalen – Westfalen und ihre Bücher. Festschrift für Hermann-Josef Schmalor zum 70. Geburtstag)

In der freiheit musicirt: Musikpraxis und -erziehung in den Taschenkalendern Kaspars von Fürstenberg - Lauert, Markus (Musiklandschaften zwischen Pader und Rhein. Verflechtung und Pluralisierung entlang des Hellwegs)

Die mündliche Prüfung. Eine Einführung - Matz, Frauke; Rogge, Michael; Rumlich, Dominik

Reusability of Germany´s total diet study food list upon availability of new food consumption data—comparison of three update strategies - Kolbaum, Anna Elena; Ptok, Sebastian; Jung, Christian; Libuda, Lars; Lindtner, Oliver (Journal of Exposure Science & Environmental Epidemiology)
Abstract Background The German total diet study (TDS)—BfR MEAL Study—established its food list in 2016 based on food consumption data of children (0.5–<5 years) and adults (14–80 years). The list consists of 356 foods selected for analysis in order to ensure ≥90% coverage of the diet. Recently, new food consumption data for children (0.5–<6 and 6–<12 years) in Germany became available, which raised the opportunity to evaluate the applicability of the MEAL food list 2016 on new data. Objective We tested the hypotheses that the MEAL food list 2016 also covers ≥90% of the diet of the new collected food consumption data, and that the selection of foods from younger children and adults was sufficient to also cover the middle age group (6–<12 years). Strategies for updating the existing food list were assessed. Methods Three approaches evaluated the reusability and potential adjustment strategies of the existing food list. Approach 1 applied the existing food list to new food consumption data. Approach 2 allowed the extension of the existing food list to improve coverage of food consumption. Approach 3 set up a new food list based on the new data. Results The MEAL food list 2016 covered 94% of the overall diet of the new collected food consumption data. The diet of the middle age group was sufficiently covered with 91%. However, coverage on main food group or population subgroup level was <90% in some cases. Approach 3 most accurately identified relevant modifications to the existing food list. 94% of the MEAL food list 2016 could be re-used and 51 new foods were identified as potentially relevant. Significance The results suggest that a high investment in the coverage of a TDS food list will lower the effort and the resources to keep data updated in the long-term. Impact There is no established approach to update a TDS food list. This study provides comparative approaches to handle newly collected food consumption data for follow-on TDS activities. The results provide useful information for institutions planning or updating a TDS. Furthermore, new food consumption data for children in Germany recently became available and are here presented for the first time.
Keywords: Public Health; Environmental and Occupational Health; Pollution; Toxicology; Epidemiology